Measurements of Strain-Rate Distributions on Material After Shpb Impact - KAWAI, M.; FUTAKAWA, M.; NAOE, T.; YAMADA, H.; XU, C. N. (Engineering Transactions, 2011)
We have proposed a sophisticated novel method of the SHPB experiment to measure the local strain-rate distributions on a surface of the specimen by using mechanoluminescent materials combined with a high-speed camera and an image intensifier. The feasibility study was made for the aluminum specimens pasted by a typical mechanoluminescent material -Eu doped SrAl2O4 film, in order to obtain the fundamental data for the method. Our results showed that SrAl2O4: Eu emitted lights as a response to the stress. Increase of the light intensity was swift enough to follow the strain change due to SHPB impact. The luminescence intensity was experimentally verified and expressed as a product of strain and strain rate. Accordingly, it can be said that this method gives a good tool for measuring time variation of local strain distributions.